2014
DOI: 10.1210/jc.2013-4050
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Parathyroidectomy on Serum FGF23 and Soluble Klotho in Hemodialysis Patients With Severe Secondary Hyperparathyroidism

Abstract: Our results suggest that the parathyroid gland is not the major site of soluble Klotho production in patients with end-stage renal disease, and the production of Klotho by other organ(s) is affected by alterations in mineral metabolism or medications taken after PTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 25 publications
4
30
2
Order By: Relevance
“…Both animal and human studies have shown that PTH administration increases FGF-23 (6-10), supporting the hypothesis that PTH is an important regulator of FGF-23. Reductions in PTH after parathyroidectomy have been associated with reductions in FGF-23 in animals with experimental renal failure and patients with ESRD (7,23,24). Therefore, it is plausible that reducing PTH concentrations with medical intervention in patients with SHPT might directly result in reductions in FGF-23 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Both animal and human studies have shown that PTH administration increases FGF-23 (6-10), supporting the hypothesis that PTH is an important regulator of FGF-23. Reductions in PTH after parathyroidectomy have been associated with reductions in FGF-23 in animals with experimental renal failure and patients with ESRD (7,23,24). Therefore, it is plausible that reducing PTH concentrations with medical intervention in patients with SHPT might directly result in reductions in FGF-23 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Purnell et al 3 in this issue of the Journal of the American Society of Nephrology suggests that the gap between blacks and whites in kidney allograft survival-an outcome measure-is narrowing significantly. This, arguably, is one of the most important measures of health disparity in ESRD management and runs counter to one of the longest standing observations differentiating black versus white transplant recipients.…”
mentioning
confidence: 99%
“…1 The treatment of severe hyperparathyroidism in patients with ESRD by either parathyroidectomy or cinacalcet generally leads to a marked decrease in serum calcium, phosphate, parathyroid hormone (PTH), and as shown more recently, serum fibroblast growth factor-23. 2,3 When such patients receive a kidney graft, generally polyclonal parathyroid hyperplasia will slowly regress because of the recovery of renal function and correction of metabolic and endocrine disturbances. This is not so with tumoral growth, where the response of parathyroid secretion and proliferation to physiologic regulatory mechanisms is reduced or lost.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Takahashi et al [21] while aiming to "determine the impact of parathyroidectomy [PTx] on serum FGF23 and soluble Klotho levels in patients with severe secondary hyperparathyroidism" suggested that "the parathyroid gland is not the major site of soluble Klotho production in patients with end-stage renal disease, and the production of Klotho by other organ(s) is affected by alterations in mineral metabolism or medications taken after PTx".…”
mentioning
confidence: 99%